2020
DOI: 10.3892/etm.2020.8770
|View full text |Cite
|
Sign up to set email alerts
|

miR‑187‑3p increases gemcitabine sensitivity in breast cancer cells by targeting FGF9 expression

Abstract: Breast cancer is the most common type of malignancy in women, which remains a significant health concern worldwide. Gemcitabine is a frequently applied anticancer pharmacological agent. However, the efficacy of gemcitabine is limited by chemoresistance. In the present study, a combination of reverse transcription quantitative-PCR, cell viability, flow cytometry, luciferase reporter assay and western blot analysis were performed to elucidate the potential effects of miR-187-3p on gemcitabine sensitivity in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…FGF9 is capable of inducing cancer stem-like cell properties in breast cancer cell lines and freshly isolated breast cancer cells through FGFR activation [ 168 ]. Furthermore, a recent publication suggested a role for FGF9 in resistance to the commonly used anti-cancer agent gemcitabine [ 169 ].…”
Section: Fgfs In Breast Cancermentioning
confidence: 99%
“…FGF9 is capable of inducing cancer stem-like cell properties in breast cancer cell lines and freshly isolated breast cancer cells through FGFR activation [ 168 ]. Furthermore, a recent publication suggested a role for FGF9 in resistance to the commonly used anti-cancer agent gemcitabine [ 169 ].…”
Section: Fgfs In Breast Cancermentioning
confidence: 99%
“…Immunotherapy and targeted therapy have emerged as potential treatment methods for breast cancer [ 4 ]. Multiple targets have been identified such as vascular endothelial growth factor, epithelial membrane protein 2, long noncoding RNAs, and so on [ 5 , 6 ]. However, more therapeutic targets are also urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have verified the overexpressed FGF9 in CAFs of gastric cancer relative to NFs, and FGF9-neutralizing antibody could hinder the enhancement effects of CAFs on gastric cancer cell metastasis, indicating the crucial role of CAFs-derived FGF9 in gastric cancer progression (Sun et al, 2015;Wang et al, 2019). The vital role of FGF9 was also proved in breast cancer (Wang et al, 2020;Wu et al, 2020); nevertheless, it is still obscure whether CAFs-derived NOVA1 plays an important role in alternative splicing in nervous system development (Jensen et al, 2000), and is linked to neurological disorders and cancer progression (Shen et al, 2015). A previous study reported that highly expressed NOVA1 was closely related to small cell lung cancer patients' poor survival and could act as a promising predictive biomarker for its prognosis (Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have verified the overexpressed FGF9 in CAFs of gastric cancer relative to NFs, and FGF9‐neutralizing antibody could hinder the enhancement effects of CAFs on gastric cancer cell metastasis, indicating the crucial role of CAFs‐derived FGF9 in gastric cancer progression (Sun et al, 2015; Wang et al, 2019). The vital role of FGF9 was also proved in breast cancer (Wang et al, 2020; Wu et al, 2020); nevertheless, it is still obscure whether CAFs‐derived FGF9 was involved in TNBC progression. Herein, FGF9 was overexpressed in TNBC CAFs, tissues and cells.…”
Section: Discussionmentioning
confidence: 99%